2021
DOI: 10.1097/jsm.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

Use of Monospot Testing in the Diagnosis of Infectious Mononucleosis in the Collegiate Student–Athlete Population

Abstract: Objective: To determine the utility of monospot testing in the diagnosis of mononucleosis in the collegiate student-athlete clinical setting. Design: Retrospective cohort study. Setting: National Collegiate Athletic Association Division I sports medicine clinic. Patients: All varsity student athletes who had a monospot test and Epstein-Barr virus (EBV) titers obtained from January 1, 2016, through March 31, 2020, (n 5 199) were included. Independent Variables: Monospot, EBV antibody titers, and liver transamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…One recent study of 199 collegiate athletes undergoing mono testing showed elevated transaminase levels in 100% of the patients with Monospot and antibody-confirmed acute IM, whereas only 3% of the cohort without acute IM had this lab abnormality. 39 However, the importance of these transient elevations and any potential correlation to splenomegaly remains unclear and are not typically used to make RTP decisions.…”
Section: Laboratory Assessmentmentioning
confidence: 99%
“…One recent study of 199 collegiate athletes undergoing mono testing showed elevated transaminase levels in 100% of the patients with Monospot and antibody-confirmed acute IM, whereas only 3% of the cohort without acute IM had this lab abnormality. 39 However, the importance of these transient elevations and any potential correlation to splenomegaly remains unclear and are not typically used to make RTP decisions.…”
Section: Laboratory Assessmentmentioning
confidence: 99%
“…On the contrary, test sensitivity is low (85% and even less than 50% in children under 6 years and in adults over 50 years). As a negative result for heterophile antibodies does not eliminate the diagnosis of IM, testing should be completed with EBV-specific serology [ 26 , 27 ].…”
Section: Infectious Mononucleosismentioning
confidence: 99%
“…Heterophile tests in current use are mono test, mono diff, and monospot. One of the most commonly used tools in the clinical setting is the monospot test, which is a latex agglutination test that detects specific heterophile antibodies made in response to an EBV infection 8. Monospot tests are frequently ordered because of ease of access and rapid results in the clinical setting; a small blood sample is collected through a simple finger stick.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…monospot test, which is a latex agglutination test that detects specific heterophile antibodies made in response to an EBV infection. 8 Monospot tests are frequently ordered because of ease of access and rapid results in the clinical setting; a small blood sample is collected through a simple finger stick. Monospot only tests for EBV and not any of the other viruses that can cause IM.…”
Section: Chronic Ebvmentioning
confidence: 99%